Proceedings of the 5th International Conference on Information Engineering for Mechanics and Materials 2015
DOI: 10.2991/icimm-15.2015.43
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Chemical Constituents of Sarcandra glabra

Abstract: From the total water extracted from Sarcandra glabra extraction part chloroform extract, nine compounds were isolated and identified as isofraxidin(1), 8-methoxy-6,7-methylenedioxy-coumarin(2), 7-methylnaringenin(3), kaemferol(4), kaemferol-3-O-rhamnopyranosyl(1→6)glucopyranoside(5), eleutheroside B 1 (6), isofraxidin-7-O-β-D-xylopyranosyl(1-3)α-D-glucopyranoside(7), rosmarinic acid (8), 3 , 4-dihydroxyphenethyl caffeate(9). Their structures were determined by spectral data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Phytochemical research was performed for the leaves of A. schimperi by chromatography and afforded a new triterpenoid ester, lupan-20-ol-3()-yl 3-hydroxyoctadecanoate (1), together with seven known triterpenoids, namely lupeol (2) [9], 28-nor-urs-12-ene-3,17-diol (3) [10], ursolic aldehyde (4) [8], 3-hydroxy-oleana-11,13(18)-dien-28-oic acid (5) [11], alagidiol (6) [12,13], oleanolic acid (7) [14] and ursolic acid lactone (8) [15] (Figure 2). The structures of the known compounds were identified by comparing their spctroscopic data with those reported in the literatures.…”
Section: Resultsmentioning
confidence: 99%
“…Phytochemical research was performed for the leaves of A. schimperi by chromatography and afforded a new triterpenoid ester, lupan-20-ol-3()-yl 3-hydroxyoctadecanoate (1), together with seven known triterpenoids, namely lupeol (2) [9], 28-nor-urs-12-ene-3,17-diol (3) [10], ursolic aldehyde (4) [8], 3-hydroxy-oleana-11,13(18)-dien-28-oic acid (5) [11], alagidiol (6) [12,13], oleanolic acid (7) [14] and ursolic acid lactone (8) [15] (Figure 2). The structures of the known compounds were identified by comparing their spctroscopic data with those reported in the literatures.…”
Section: Resultsmentioning
confidence: 99%
“…Sarcandroside B C 53 H 86 O 22 212. Lupeol C 30 H 50 O S. glabra, whole plant EtOH [ 53 ] 213. 24-Hydroxylupeol C 30 H 50 O 2 214.…”
Section: Chemical Constituentsmentioning
confidence: 99%
“…Scopoletin C 10 H 8 O 4 S. glabra, whole plant DCM [ 32 , 86 ] 232. Eleutheroside B 1 C 17 H 20 O 10 S. glabra, whole plant EtOH [ 53 ] 233. 3,3′-Biisofraxidin C 22 H 18 O 10 S. glabra, whole plant EtOH [ 85 ] 234.…”
Section: Chemical Constituentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the IR spectroscopy of IF showed several prominent absorption spectra (KBr) including 3200-3500 cm −1 (the broad peak related to the hydroxyl group (OH − ), 2900-3000 cm −1 (medium, C-H), 1675-1705 cm −1 (strong, C=O), 1570-1600 cm −1 (medium, C=C aromatic), 1600-1680 cm −1 (weak, C=C), and 1030-1300 cm −1 (medium, C-O) [92,93]. In another study, the noticeable results of IR spectroscopy of IF isolated from Sarcandra glabra were included 3298, 2981, 2941, 1705, 1606, 1574, 1302, 1036 that could be interpreted based on the aforementioned results [94]. The range of the chemical shifts (δ) and coupling constants (J) of the 1 H and 13 C NMR study of IF has been shown in Table 2.…”
Section: Identification and Structure Elucidationmentioning
confidence: 99%